A HETEROGLOSSIA OF BIG DATA KNOWLEDGES - Herrie, Maja Bak (The Nordic Journal of Aesthetics, 2022)
Review of UNCERTAIN ARCHIVES: CRITICAL KEYWORDS FOR BIG DATA EDITED BY NANNA BONDE THYLSTRUP, DANIELA AGOSTINHO, ANNIE RING, CATHERINE D’IGNAZIO AND KRISTIN VEEL CAMBRIDGE: THE MIT PRESS, 2021. 640 PAGES ISBN: 9780262539883